Phenologic answer of the arboreal vegetation in Peruvian southern lomas (Mejia-Arequipa) in relation to "El Niño 1997-98" event - Talavera, Carmelo (1999)
This work present the evaluation of phenologic behave of the arboreal vegetation in order to determine its possible use as biological indicator of "El Niño" events. The evaluated trees were Caesalpinia spinosa, Duranta armata, Carica candícans, and Cítharexylum f1exuosum. The results showed a high variation in phenologic answer. C. spínosa for example began flowering before shoot in 1995 and 1996; in 1997 began before, but had a short duration, and in 1998 it had presented in a late and brief period, while the foliage covering had been maintaíned constant. In the case of D. armata and C. flexuosum the flowering occurred after the shoot. But both cases during 1998 did not present flowering; and C. candicans presented Iloweríng before the shoot, but with high variability in flowering size.